2016
DOI: 10.1186/s13638-016-0674-5
|View full text |Cite
|
Sign up to set email alerts
|

On the human body communications: wake-up receiver design and channel characterization

Abstract: By modulating the electric field induced to a human body, it is possible to transfer data wirelessly using the body as a transmission medium. This method is referred to as human body communication (HBC), which has multiple advantages in comparison with the traditional radio frequency (RF) communication. First, it alleviates the traffic load from the radio channels, which are becoming more and more congested, as the number of connected wireless devices increases rapidly. Second, HBC can potentially provide high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Improving the sensitivity can also be realized with architectures allowing a better filtering of signals, e.g., super-heterodyne (SH) or super regenerative (SR) architectures. The authors of [ 107 ] introduced a SR-based WuRx with a power consumption of 40 μW and a sensitivity of −97 dBm. The decoding mechanism is performed on an off-the-shelf complex programmable logic device (CPLD), requiring much higher power than most recently published WuRx decoders.…”
Section: Energy Managementmentioning
confidence: 99%
“…Improving the sensitivity can also be realized with architectures allowing a better filtering of signals, e.g., super-heterodyne (SH) or super regenerative (SR) architectures. The authors of [ 107 ] introduced a SR-based WuRx with a power consumption of 40 μW and a sensitivity of −97 dBm. The decoding mechanism is performed on an off-the-shelf complex programmable logic device (CPLD), requiring much higher power than most recently published WuRx decoders.…”
Section: Energy Managementmentioning
confidence: 99%
“…In the LPWAN, wireless communications range outdoors can be over 10 km [63] and in indoors one base station can cover a large real-estate [64]. Whereas, in a traditional WSN communications range of the sensor node is usually some tens of meters [65]. Figure 9 shows main differences between the WSN the LPWAN.…”
Section: A Wake-up Receiver Architecturesmentioning
confidence: 99%
“…In [60] and [77] authors have shown that hierarchical architecture and its analytical energy efficiency model introduced in [58] can also be applied for WBAN scenario. Further, in [65] the wake-up radio and DCR based network energy consumption comparison is discussed in WBANs case. Here are shown WUR and DCR energy efficiency comparison results which are calculated using four different WUR parameters, which are shown in Table 1.…”
Section: De Rxmentioning
confidence: 99%
“…The latter, however, is less of a concern for amplitude modulation schemes. An SR-based WuRx [ 10 ] demands 40 of power and emphasizes an excellent sensitivity of . The decoding mechanism is performed on an off-the-shelf complex programmable logic device (CPLD), requiring much higher power than most of the recently published WuRx decoders [ 1 , 3 , 7 , 8 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%